A prospective analysis of dietary energy density at age 5 and 7 years and fatness at 9 years among UK children. - Johnson, L; Mander, A; Jones, L; Emmett, P; Jebb, SA (2008)
OBJECTIVE: To analyse whether high dietary energy density (DED) is associated with increased fat mass and risk of excess adiposity in free-living children. DESIGN: Longitudinal, observational cohort study. SUBJECTS: Six hundred and eighty-two healthy children from the Avon Longitudinal Study of Parents and Children. MEASUREMENTS: Diet was assessed at age 5 and 7 years using 3-day diet diaries, and DED (kJ g(-1)) was calculated excluding drinks. Fat mass was estimated at age 9 years using Dual-Energy X-ray Absorptiometry. To adjust for body size, fat mass index (FMI) was calculated by dividing fat mass (kg) by height (m(5.8)). Excess adiposity was defined as the top quintile of logFMI. RESULTS: Mean DED at age 5 years was higher among children with excess adiposity at age 9 years compared to the remaining sample (8.8+/-0.16 vs 8.5+/-0.07 kJ g(-1)), but there was no evidence of an association with excess adiposity at age 9 years (odds ratio (OR)=1.14, 95% confidence interval (CI) 0.90-1.44) after controlling for potential confounders. Mean DED at age 7 years was higher among children with excess adiposity compared to the remaining sample (9.1+/-0.12 vs 8.8+/-0.06 kJ g(-1)) and a 1 kJ g(-1) rise in DED increased the odds of excess adiposity at 9 years by 36% (OR=1.36, 95% CI 1.09-1.69) after controlling for potential confounders. CONCLUSION: Higher DED at age 7 years, but not age 5 years, is a risk factor for excess adiposity at age 9 years, perhaps reflecting deterioration in the ability to compensate for extra calories in an energy-dense diet. DED tracks strongly from age 5 to 7 years suggesting intervention to alter dietary habits need to commence at younger ages to prevent the formation of preferences for energy dense foods.